Developing Socially Caring Characters Through Extracurricular PMR SMAN 20 Bandung - Kumala Sari, Dyah Ayu Ratna; Rahmat, Munawar; Fakhruddin, Agus (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This study aims to identify the social care programs that exist in PMR activities at SMAN 20 Bandung, the methods of developing social care characters that are applied, and the realization of these characters in participating students. This research uses a qualitative approach with descriptive method, and data collection techniques including interviews, observations, and document studies. The subjects of this study consisted of PMR coordinators, PMR trainers, and students involved in PMR extracurricular activities. The results showed that PMR extracurricular activities effectively contributed to the development of students' social care character. The methods used in the development of social care characters are able to increase students' social awareness and responsibility. The results of this study show that PMR extracurricular activities contribute to the development of students' social care character, and can be a recommendation for strengthening Islamic religious education through extracurricular activities at the school.